2006
DOI: 10.1111/j.1399-0039.2006.00622.x
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of HLA class I and II alleles and haplotypes to the investigation of the evolutionary history of Tunisians

Abstract: The frequencies of HLA class I and class II alleles and haplotypes of 104 healthy unrelated Tunisians were analyzed by high-resolution PCR-reverse dot blot hybridization, and was compared with other Mediterranean and Sub-Saharan Africans using genetic distances measurements, Neighbor-joining dendrograms, correspondence, and extended haplotypes analysis. The most frequent HLA class I A alleles were A*02, A*24, and A*30, while the most frequent B alleles were B*44, followed by B*50, B*51, and B*07. Among HLA cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
39
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 29 publications
13
39
0
Order By: Relevance
“…The highest frequencies of HLA-A alleles were observed in the allele group HLA-A ⁄ 02 (23.3%). This value is also highest in other Mediterranean and African populations [12,13,23,[24][25][26][27][28][29][30]. HLA-A ⁄ 01 (11.4%) has a similar distribution to those reported in Moroccan (12.1%) [12,31,32], and Algerian (11.9%) [14] and other populations [32] and Tunisians (17.5%) [34] but lower than those reported for Tunisian Berbers (24.8%) [39].…”
Section: Hla Allele Frequenciessupporting
confidence: 79%
See 2 more Smart Citations
“…The highest frequencies of HLA-A alleles were observed in the allele group HLA-A ⁄ 02 (23.3%). This value is also highest in other Mediterranean and African populations [12,13,23,[24][25][26][27][28][29][30]. HLA-A ⁄ 01 (11.4%) has a similar distribution to those reported in Moroccan (12.1%) [12,31,32], and Algerian (11.9%) [14] and other populations [32] and Tunisians (17.5%) [34] but lower than those reported for Tunisian Berbers (24.8%) [39].…”
Section: Hla Allele Frequenciessupporting
confidence: 79%
“…The frequency of this haplotype in the Cyrenaica population is higher compared to other North African populations, such as Tunisians (HF: 1.8%) [13] and Tunisians Ghannouch area (HF: 2.5%) [33].…”
Section: Hla-a -B and -Drb1 Haplotype Frequencymentioning
confidence: 96%
See 1 more Smart Citation
“…This overlapping of allele distribution among Caucasian, Tunisian, and African populations can likely be explained by the invasion of North Africa by the Romans, oriental Arabic Muslims, and some sub-Saharan tribes hundreds of years ago and confirms the mixed origin of the Tunisian population as suggested by numerous studies on other markers, such as HLA and Duffy (Ayed et al 2004;Hajjej et al Sellami et al 2008). Besides the fundamental report on the genetic background of the Kell blood group system, this work will be useful to expand our red blood cell panel (manufactured in our laboratory) for rare phenotypes (such as KEL:6,7).…”
Section: Resultsmentioning
confidence: 75%
“…Graft survival is superior in sibling pairs having both the same serologically defined HLA antigens and a nonreactive in vitro mixed lymphocyte proliferative response when compared to randomly match deceased donors treated with the same immunosuppressive drugs (6). Polymorphism in the HLA system is used as a tool for anthropological studies, as genetic distances and correspondence analysis demonstrated that the allele and haplotype distribution of class I and class II loci are racially and geographically restricted (7,8).This prompted the use of HLA class I and class II phenotype and haplotypes in different ethnic groups for the analysis of the origin, migration and the degree of admixture of populations (9). HLA gene and haplotype frequencies have been described in different racial groups (10).…”
Section: Introductionmentioning
confidence: 99%